2022
DOI: 10.3389/fsurg.2022.847213
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Menstrual Blood-Derived Stem Cell Transplantation for Intrauterine Adhesions

Abstract: An increasing number of women experience intrauterine adhesion as a result of intrauterine operations, such as induced abortion, which can cause infertility, recurrent abortion and amenorrhea. Although some strategies have been applied clinically, such as hysteroscopy adhesiolysis of intrauterine adhesions, the results have not been promising. As regenerative medicine develops, research on menstrual blood-derived stem cell transplantation is increasing due to the properties of these cells, including self-renew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(59 reference statements)
0
4
0
Order By: Relevance
“… 19 Endometrial mesenchymal stem cells (EnMSCs) are located in the endometrium and can be extracted from menstrual blood and used to treat diseases such as intrauterine adhesions. 20 In this study, we demonstrated that purified EnMSCs can be stably cultured with relatively superior mitochondrial function compared to that of primary endometrial stromal cells (ESCs) in a mouse model. We also found that the transfer of mitochondria from EnMSCs can improve oocyte quality and fertility in aged mice.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“… 19 Endometrial mesenchymal stem cells (EnMSCs) are located in the endometrium and can be extracted from menstrual blood and used to treat diseases such as intrauterine adhesions. 20 In this study, we demonstrated that purified EnMSCs can be stably cultured with relatively superior mitochondrial function compared to that of primary endometrial stromal cells (ESCs) in a mouse model. We also found that the transfer of mitochondria from EnMSCs can improve oocyte quality and fertility in aged mice.…”
Section: Introductionmentioning
confidence: 93%
“…Studies in the past decade have shown that mitochondria from mesenchymal stem cells (MSCs) can regenerate and repair damaged cells or tissues 19 . Endometrial mesenchymal stem cells (EnMSCs) are located in the endometrium and can be extracted from menstrual blood and used to treat diseases such as intrauterine adhesions 20 . In this study, we demonstrated that purified EnMSCs can be stably cultured with relatively superior mitochondrial function compared to that of primary endometrial stromal cells (ESCs) in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, MenSC have already been extensively applied in preclinical studies and in some clinical research, with many of them revealing positive and successful outcomes in a variety of diseases. Gynecological applications of this novel therapy are summarized in Figure 2 [13,[37][38][39][40][41][42][43][44]. Some novel strategies for the use of MenSC in treatment have been comprehensively studied.…”
Section: Mensc-based Therapies Novel Approachesmentioning
confidence: 99%
“…eSPCs have been found to play a crucial role in the regeneration and repair of the endometrium [ 54 , 126 , 127 ]. We therefore would envisage eSPCs to be involved in the persistent aberrations in the functionalis layer of each successive cycle, associated with the implantation process and subsequent pregnancy establishment in RRF.…”
Section: Applications In Clinical Management Of Rrfmentioning
confidence: 99%
“…The authors concluded that stem cells derived from menstrual blood may have a role in repairing the damaged endometrium, which could be due to the engagement of angiogenesis mediated by stem cells derived from menstrual blood [ 151 ]. Therapy with autologous eMSCs derived from menstrual blood has also shown promise, accelerating the healing process of damaged endometrium by inducing self-renewal, differentiation, angiogenesis, anti-inflammation, and immunomodulation [ 127 ]. Numerous issues must, however, be addressed before treatments can be introduced to clinical practice, such as transplanted cell dosage, and administration route.…”
Section: Applications In Clinical Management Of Rrfmentioning
confidence: 99%